Diagnostic potential of IL6 and other blood-based inflammatory biomarkers in mild traumatic brain injury among children - Chiollaz, Anne-Cécile; Pouillard, Virginie; Habre, Céline; Seiler, Michelle; Romano, Fabrizio; Spigariol, Fabian; Ritter Schenk, Céline; Korff, Christian; Maréchal, Fabienne; Wyss, Verena; Gruaz, Lyssia; Montaner, Joan; et al. (Frontiers in Neurology, 2024)
Objectives Inflammatory biomarkers, as indicators of biological states, provide a valuable approach for accurate and reproducible measurements, crucial for the effective management of mild traumatic brain injury (mTBI) in pediatric patients. This study aims to assess the diagnostic utility of blood-based inflammatory markers IL6, IL8, and IL10 in children with mTBI, including those who did not undergo computed tomography (CT) scans. Methods A prospective multicentric cohort study involving 285 pediatric mTBI patients was conducted, stratified into CT-scanned and non-CT-scanned groups within 24 h post-trauma, alongside 74 control subjects. Biomarker levels were quantitatively analyzed using ELISA. Sensitivity and specificity metrics were calculated to determine the diagnostic efficacy of each biomarker. Results A total of 223 mTBI patients (78%) did not undergo CT scan examination but were kept in observation for symptoms monitoring at the emergency department (ED) for more than 6 h (in-hospital-observation patients). Among CT-scanned patients (n = 62), 14 (23%) were positive (CT+). Elevated levels of IL6 and IL10 were found in mTBI children compared to controls. Within mTBI patients, IL6 was significantly increased in CT+ patients compared to both CT– and in-hospital-observation patients. No significant differences were observed for IL8 among the compared groups. IL6 yielded a specificity of 48% in identifying CT– and in-hospital-observation patients, with 100% sensitivity in excluding all CT+ cases. These performances were maintained whether IL6 was measured within 6 h or within 24 h after the trauma. Conclusion The inflammatory marker IL6 emerges as a robust biomarker, showing promising stratification value for pediatric mTBI patients undergoing CT scans or staying in observation in a pediatric ED.